2009
DOI: 10.1016/s0929-6646(09)60082-6
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for Ambulatory-care-sensitive Conditions in Taiwan Following the SARS Outbreak: A Population-based Interrupted Time Series Study

Abstract: Admission rates for most ACSCs, except for diabetes, did not change in the post-SARS period. The reductions in outpatient utilization during the SARS outbreak did not appear to affect adversely admissions for most ACSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 21 publications
(45 reference statements)
1
65
0
2
Order By: Relevance
“…Bloomgarden et al [17] stated that mortality rates from pneumonia among patients with diabetes in Hong Kong (age 75) exceed mortality rates in this age group from cardiovascular disease and cancer [18]. Similar evidence of risk amid persons with diabetes has been reported for the two earlier CoV infections: SARS in 2002 [19,20] and MERS in 2012 [21].…”
Section: Diabetesmentioning
confidence: 79%
“…Bloomgarden et al [17] stated that mortality rates from pneumonia among patients with diabetes in Hong Kong (age 75) exceed mortality rates in this age group from cardiovascular disease and cancer [18]. Similar evidence of risk amid persons with diabetes has been reported for the two earlier CoV infections: SARS in 2002 [19,20] and MERS in 2012 [21].…”
Section: Diabetesmentioning
confidence: 79%
“…To date, there have been only limited experimental studies directly addressing the role of hyperglycemia in the pathogenesis and prognosis of viral respiratory diseases [5][6][7][8] . However, it has been shown that elevated blood glucose levels can directly increase glucose concentrations in airway secretion.…”
Section: Importance Of Glycemic Control In Those With Coexistence Of mentioning
confidence: 99%
“…Studies during the SARS-CoV-1 outbreak showed that while hospitalisations for diabetes plummeted during the crisis, these skyrocketed afterwards. 90 During the present crisis, there has already been fewer admissions for stroke and heart-attack. The concern is that the incidence is the same but cautious/frightened patients are not presenting for care.…”
Section: Introductionmentioning
confidence: 99%